2017
DOI: 10.1371/journal.pone.0184096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trabeculectomy on visual field progression in Japanese progressive normal-tension glaucoma with intraocular pressure < 15 mmHg

Abstract: We examined the effectiveness of trabeculectomy in decreasing the slope of mean deviation (MD) in Japanese patients with progressive normal-tension glaucoma (NTG) at low intraocular pressure (IOP) levels. The charts of patients who had undergone initial trabeculectomy with adjunctive mitomycin C for progressive NTG with medically controlled IOP < 15 mmHg in 2010–2013 were retrospectively reviewed. Seventeen eyes of 13 NTG patients who had undergone at least 5 times of visual field (VF) examinations in both of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…during the following 9 months. When comparing the VF changes over one year in the present study with those obtained in other trials 1,[18][19][20][21][22] , the more advanced glaucomatous damage in our population needs to be considered. An important finding is that RNFL thickness significantly declined over the one-year study period.…”
Section: Discussionmentioning
confidence: 89%
“…during the following 9 months. When comparing the VF changes over one year in the present study with those obtained in other trials 1,[18][19][20][21][22] , the more advanced glaucomatous damage in our population needs to be considered. An important finding is that RNFL thickness significantly declined over the one-year study period.…”
Section: Discussionmentioning
confidence: 89%
“…2 Surgical management of NTG patients is especially challenging, since very low IOPs are required to achieve therapeutic reduction from baseline levels within the normal range. 5 Consequently, surgeons face a narrow therapeutic window between these low target pressures and potentially dangerous hypotonus pressures. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Trabeculectomy has traditionally been the first-line surgical option for NTG patients, since it is capable of meeting low IOP goals in NTG patients, 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 even when single-digit postsurgical IOPs are required. 13 However, as a relatively invasive procedure, trabeculectomy has historically suffered from high complication rates, including long-term hypotony especially in NTG patients, ranging from 28 to 30%, 6 , 12 which can lead to cataract formation, 14 hypotonous maculopathy, 6 , 13 and choroidal detachment.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients may continue to experience disease progression, although they have IOP within the normal range (Shiose et al 1991;Anderson et al 2003). Many studies (Aoyama et al 2010;Jayaram et al 2016;Schultz et al 2016;Naito et al 2017;Oie et al 2017) have shown that trabeculectomy can significantly reduce IOP and prevent progression of visual field disorders. We presume that maintenance of visual function can be expected when trabeculectomy is performed in glaucoma patients with IOP maintained in the normal range by topical medications.…”
Section: Total Case (%)mentioning
confidence: 99%